(untitled) (CIPEEX, 2022)
MINERAL WATER IS CONSIDERED A UNIVERSAL HIGH CONSUMPTION PRODUCT. THUS, IT IS NECESSARY THE MONITORING OF PARAMETERS THAT GUARANTEE THE CONTINUITY OF PRODUCTION, SALE AND QUALITY OF THESE PRODUCTS. THE MINERAL WATERS ARE IN THE SO-CALLED "WATERS SUITABLE FOR CONSUMPTION" AND BY RDC NO. 274/2005 OF THE NATIONAL HEALTH SURVEILLANCE AGENCY (ANVISA) ARE THOSE OBTAINED DIRECTLY FROM NATURAL SOURCES OR BY EXTRACTION OF GROUNDWATER, CHARACTERIZED BY A DEFINED AND CONSTANT CONTENT OF CERTAIN MINERAL SALTS, TRACE ELEMENTS AND OTHER CONSTITUENTS, TAKING ACCOUNT OF NATURAL FLUCTUATIONS. THIS LEGISLATION, ALONG WITH RDC 275/2005, OF THE SAME BODY, DEFINE THE IDENTITY AND QUALITY OF THIS PRODUCT. CONSIDERING THIS CONTEXT, THE OBJECTIVE OF THIS WORK WAS TO EVALUATE PHYSICAL-CHEMICAL PARAMETERS AND LABELING OF SEVEN MINERAL WATER BRANDS COMMERCIALIZED IN ANÁPOLIS - GO. THE SEVEN BRANDS (THREE 500ML EACH) WERE OBTAINED IN THE LOCAL MARKET AND GUIDED WITH THEIR ORIGINAL PACKAGING TO THE UNIEVANGLICA FOOD ANALYSIS LABORATORY, WHERE THE ANALYZES WERE CARRIED OUT. EACH SAMPLE WAS ANALYZED FOR THE LABELING ITEMS DEFINED IN RDC Nº54 / 2013, RDC Nº360 / 2003 AND LAW Nº 7.841 / 1945 AND THE PHYSICOCHEMICAL PARAMETERS: PH, TOTAL DRY SOLIDS, CHLORIDES, AMMONIA, SULFATES, TOTAL ALKALINITY, HARDNESS, TURBIDITY AND OXIDIZABLE SUBSTANCES. THE LABELS OF THE SEVEN SAMPLES PRESENTED ACCORDINGLY. THE PRODUCT LABEL IS INTENDED FOR CONSUMER ORIENTATION AND INFORMATION, SO IT SHOULD BE EASY TO UNDERSTAND. IN ADDITION TO GUIDING THE CONSUMER, LABELING HELPS PREVENT FRAUD AND ASSISTS IN THE TRACEABILITY OF PRODUCTION. IN THE PHYSICAL-CHEMICAL EVALUATIONS, ONLY ONE SAMPLE WAS AT ODDS WITH THE PARAMETER OF OXIDIZABLE SUBSTANCES. THE VALUES €‹€‹OBTAINED RANGED FROM: PH 5.04 TO 7.13 (4 TO 10); TOTAL DRY SOLIDS FROM 0.015MG / L TO 0.239MG / L (UP TO 1000MG / L); CHLORIDES 12.90MG / L TO 39.70MG / L (<250MG); AMMONIA ABSENT IN ALL ANALYZED BRANDS; HARDNESS FROM 40.42MG / L TO 145.84MG / L (<500MG / L), TURBIDITY FROM 0.0NTU TO 0.52NTU AND OXIDIZABLE SUBSTANCES FROM 1.15MG / L TO 2.55MG / L (2.0MG / L) . THE PHYSICOCHEMICAL ANALYZES ARE AIMED AT EVIDENCING THE QUALITY OF THE PRODUCTS, BEING KEY POINTS IN THIS PRODUCT, TO DEMONSTRATE THE POTABILITY AND ORIGIN OF THESE WATERS. THE ANALYZES CARRIED OUT IN THIS WORK DEMONSTRATED THAT OF THE SEVEN SELECTED BRANDS, ONLY ONE BRAND APPEARED IN DISAGREEMENT IN ONE OF THE PARAMETERS ANALYZED, DEMONSTRATING THAT THE PACKAGING AND MARKETING OF THESE PRODUCTS ARE, IN GENERAL, FOLLOWING THE RECOMMENDATIONS OF GOOD PRACTICES. HOWEVER, FOR THE COMPLETE GUARANTEE OF SAFETY FOR THE CONSUMPTION, THE MICROBIOLOGICAL ANALYZES INDICATED BY THE CURRENT LEGISLATION WILL BE NECESSARY.